Comparative thinking of three contemporary Filipino educators on quality and quantity education - Corpuz, Nenita Raguindin 1947- (s.n.], 1971)
The objective of this study is to contribute to the desired advancement of Philippine education by providing a deeper understanding and insight into one of the foremost and still unsolved educational problems of the country today which is the problem on quality and quantity education. This was made possible in this study through the presentation and comparison of the thinking on the problem of three of the foremost contemporary Filipino educators, Drs. Bernardino, Isidro and Orata. This study made use of the documentary analysis and interview methods in obtaining the needed data.